2013
DOI: 10.1186/2228-5326-3-41
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel synthesis, characterization, and optical properties of Gd3+-doped CdO sub-micron materials

Abstract: Highly crystalline Gd 3+ -doped cadmium oxide micro-structure was synthesized by calcining the obtained precursor of a sol-gel reaction. The reaction was carried out with cadmium nitrate (Cd(NO 3 ) 2 ·4H 2 O), gadolinium oxide, and ethylene glycol (C 2 H 6 O 2 ) reactants without any additives at 80°C for 2 h. The resulting gel was calcined at 900°C with increasing temperature rate of 15°C/min for 12 h in a furnace. As a result of heating, the organic section of the gel was removed, and the Gd 3+ -doped cadmiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…2b-e, the small particles were observed over the surface of the particles. These small particles are known as uncus (Alemi et al 2013), and were formed as a result of layered growth. It was also observed that due to increase in doping value, the number of uncus particles and heterogeneity in particle size were also increased.…”
Section: Sem Studiesmentioning
confidence: 99%
“…2b-e, the small particles were observed over the surface of the particles. These small particles are known as uncus (Alemi et al 2013), and were formed as a result of layered growth. It was also observed that due to increase in doping value, the number of uncus particles and heterogeneity in particle size were also increased.…”
Section: Sem Studiesmentioning
confidence: 99%
“…In this technique, characteristics of films relying upon preparation conditions similar to spray rate, nozzle-substrate and the substrate temperature [11]. CdO is one of material considered to be a model n-type semiconductor [12], with cubic structure where each ions collared by six ions of different electric charge [13,14]. In this work, the variation of the optical, structural properties of CdO thin films obtained by spray pyrolysis method was studied as a function of the Ce doping with various concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…In this technique, characteristics of films relying upon preparation conditions similar to spray rate, nozzle-substrate and the substrate temperature [1] . CdO is an n-type semiconductor [11] , with cubic structure where each ions collared by six ions of different electric charge [12] . It is now well voluntary control that the CdO appears many highest quality properties, which produced it a suitable as a transparent conductive oxide (TCO) [13] .…”
Section: Introductionmentioning
confidence: 99%